Improving Smash Accuracy in Badminton Athletes: A Systematic Literature Review - Muhammad Rizky Putra Hadi; Mashud (Jurnal Pendidikan Jasmani (JPJ), 2025)
Smash accuracy is one of the key factors in badminton performance. To analyze and evaluate the effectiveness of various training methods in improving smash accuracy among badminton athletes. A systematic literature review was conducted using the PICO framework and PRISMA guidelines with predetermined inclusion and exclusion criteria. Article searches were performed on Google Scholar using keywords related to training methods and badminton smash accuracy. After the screening process, 11 articles met the inclusion and exclusion criteria. Among the 11 reviewed articles, drill training methods demonstrated the highest consistency in improving smash accuracy in badminton athletes. Eight articles explicitly showed that drill methods had positive and significant effects on smash accuracy. Variations of drill methods such as V-Drill technique, drills with specific targets, and integrated training models also proved effective. Comparative analysis between methods revealed that more focused and targeted approaches (such as directional smash training and drilling methods compared to target games) tended to be more effective than complex methods. Drill training methods represent the gold standard for improving smash accuracy in badminton athletes, with consistent effectiveness across various age groups and skill levels. Future research should investigate the effectiveness of these methods on elite athletes and conduct longitudinal studies to understand long-term skill retention.